INNOVATION FUNGSI PERGURUAN TINGGI DITENGAH PUSARAN PEMILIHAN KEPALA DAERAH TAHUN 2018 (Universitas Suryakancana, 2018)
The function of higher education as a learning forum for students and the community, a forum for the education of prospective leaders of the nation, as a center for the development of science and technology, as a center for policy studies and moral power tp find and discover national development centers. Progress of a nation’s civilization. Specifically in the context of local democracy in the election of regional heads (PILKADA) of provinces/cities in 2018 as part of the implementation of local democracy.Based on this, to facilitate the limitation in making this paper, the identification of the problem consists of: How is the role of higher education in the implementation of the 2018 election? Thus the tertiary institution must be able to take part in correcting the problem of regulation, the system of administration and the quality of human resource needed in a local political contest or the Regional Election Committe, especially the 2018 regional election. Keywords: Democracy; Local Democracy; Regional Head Elections; Political Contestation.